The Macroeconomic Effects of Corporate Income Tax Rate Reductions - Mohamad Ali, Shaharudin (2008)
This study examines the impact of the corporate income tax rate reduction on the Malaysian macro economy and its relationship with economic growth. The reduction in the tax rate coincides with the Keynesian theory that suggests a government should intervene to halt sluggishness in the economy by lowering the corporate income tax rate or escalating public spending, or both as it has a relationship with economic growth. The government could correct the sluggishness by raising their spending or lowering tax rate to transfer funds from public to private sector in terms of this tax incentive or increase public spending to stimulate aggregate demand for the goods and services in the country. Advocates claim that the country's economic growth during the 1990s was evidence on how this theory works. The multiplying effect of this short-term economic stimulus is that when companies increase their investments: more jobs are created, increase in productivity, boost exports, generate more profits and paying more tax to the Government that will improve budget position and gross domestic product and the economy starts growing again. When the economy starts grow again, more foreign investments both through direct investment and portfolio capital will be attracted to do business in this country as they seek opportunity for profits and growth. Advocates claim that the country's economic growth during the 1990s was evidence on how the theory works. There are many findings published in the developed economies discuss the macroeconomic effect of the corporate income tax rate on the economy and its relationship with the economic growth. However, there is no documented evidence avail so far to address this topic in the Malaysian context and research in this area is still lacking as well. Data collected from published reports by the Treasury Department, the Statistics Department, the Central Bank of Malaysia and cross-checked against the International Monetary Fund publications. A time series econometric analysis was used to study the macroeconomic effect of the reduction in the corporate income tax rate and the relationship with the country's economic growth. This method normally employed by researchers to ascertain the macroeconomic effect of changes in the government policy. The findings indicate that lowered corporate income tax rate had minimal effect on the country's macro economy. All selected macroeconomic variables had insignificant effect with the reduction in the tax rate except for the foreign exchange rate and gross domestic product (GOP). The significant level for both variables is 0.01. The significant increased in the exchange rate might not directly due to the reduction in the tax rate but instead from the changes in the Government monetary policy. The significant increased in the GOP confirms with the Keynesian theory that claim lower tax rate has relationship with the country's economic growth. This study, however, do not supports the application of the Keynesian theory in the Malaysian context especially when the whole world is currently facing with the economic uncertainty. Malaysia currently has not incurred any budget surplus or intention to increase its public debt to finance this tax incentive. Thus the Government has no avail means to finance the short-term reduced in their real income whenever they reduced the corporate income tax rate. This short-term stimulus incentive needs to be backed up either by budget surplus or borrowing money otherwise the nation savings are likely affected which will aggravate the country's future economic growth. Surprisingly, lowered tax rate is found not effective in attracting long-term foreign investments to do business in this country. Whilst the transformation done on the tax assessment system in 2000 was found not significantly improving the country's macro economy but it has significant relationship with the Government Financial Position group. The significant level is at 0.10. The findings are inconclusive for the period under study.